The influence of work discipline and work stress on employee performance (Case study at CV Rimba Jaya) - Gustama, Gala; Tarmidi, Didi (Technium Social Sciences Journal, 2021)
This study aims to determine how the description of work discipline, work stress, and employee performance, and to determine how the influence of work discipline and work stress on employee performance at CV Rimba Jaya. The factors tested in this study were work discipline and job stress as independent variables, while employee performance was the dependent variable. The research method used in this research is descriptive and verification methods. The population in this study were employees at CV Rimba Jaya. The sampling technique used in this study is a non-probability sampling technique with a saturated sampling technique, so that the total number is 65 people. The analytical method used in this study is multiple linear regression analysis using the Statistical Package for Social Sciences (SPSS) Vers.25.00. The results showed that work discipline and work stress have an effect on employee performance at CV Rimba Jaya. The magnitude of the influence of work discipline and work stress on employee performance is 74.6%.